Beneficial effect of camel milk in diabetic nephropathy - Agrawal, R. P.; Dogra, R.; Mohta, N.; Tiwari, et al., R. (Acta Biomedica Atenei Parmensis, 2009)
Diabetic nephropathy is originally microvascular in nature and is widely considered an important complication of diabetes. The present study was carried out to determine the efficacy of camel milk in controlling diabetic nephropathy. Twenty-four type-1 diabetic patients were randomly recruited from the outpatient diabetic clinic in PBM Hospital, Bikaner, India. All subjects gave their written consent before participation in the study. Patients with any acute metabolic complications were not included in the study. Eligible patients entered a run–in period of 1 month in which they were oriented to achieve the best possible glycemic control through standardized diet, standardized exercise regimen and insulin administration. During this period frequent monitoring of blood sugar was performed to maintain euglycemia. At the end of the run-in period, a base line evaluation was performed, then these patients were given camel milk in addition with usual care for six months. Urine microalbumin and blood sugar was measured twice a week before breakfast and dinner. There was a significant improvement in the microalbuminuria (119.48±1.68 to 22.52±2.68; p<0.001) after receiving camel milk for 6 months. A significant reduction in the mean dose of insulin for obtaining glycemic control was achieved (41.61±3.08 to 28.32±2.66; p<0.01). This study was performed to observe the role of camel milk in controlling microalbuminuria levels in type-1 diabetic patients. It was observed that after adding camel milk to the usual regimen an improvement in microalbuminuria was reached (119.48±1.68 to 22.52±2.68; p<0.001). This may be due to good glycemic control or to the direct effect of camel milk. The mechanism behind this effect is still unknown.